Hubungan Antara Citra Tubuh Dan Intensitas Penggunaan Media Sosial Dengan Ketidakpuasan Bentuk Tubuh Pada Remaja: The Relationship Between Body Image and Intensity of Social Media Use and Body Shape Dissatisfaction in Adolescents - Ovi Ambar Taluki Asih; Zaki Nur Fatmawati (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Adolescent development is characterized by significant physical changes that shape self-perception and psychological adjustment. Specific Background: In the digital era, intensive social media exposure and body image perception are closely associated with body shape dissatisfaction among adolescents. Knowledge Gap: Although prior studies have examined these variables separately, limited research has analyzed body image and social media intensity simultaneously within a specific Indonesian adolescent context. Aims: This study examines the relationship between body image and intensity of social media use with body shape dissatisfaction among adolescents. Results: Based on a quantitative correlational design involving 305 students aged 15–19 years, findings reveal that social media use intensity shows a highly significant relationship with body shape dissatisfaction (p = 0.00), while body image also demonstrates a significant relationship (p = 0.02), with social media intensity presenting a stronger statistical contribution. Novelty: This study integrates psychological and behavioral variables concurrently within a localized adolescent population in Indonesia. Implications: The findings provide empirical evidence supporting structured educational programs promoting critical and balanced social media engagement to address adolescent body dissatisfaction. Keywords: Body Image, Body Dissatisfaction, Social Media Intensity, Adolescents, Social Comparison Key Findings Highlights: Higher frequency and duration of online engagement correspond with elevated dissatisfaction levels. Negative self-perception is statistically linked with unfavorable physical evaluation. Concurrent analysis clarifies differential statistical contribution between predictors.